The role of mitochondrial dysfunction in ovarian granulosa cells in polycystic ovary syndrome - Xuejun Yan; Dan Ma; Rongnian Li; Jing Xu; Ying Zou; Minmin He (Endocrine Connections)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder that significantly impacts women’s reproductive capabilities and metabolic health, leading to a range of complications that can affect their quality of life. Recent studies have highlighted mitochondrial dysfunction as a crucial factor in the complex pathogenesis of PCOS, suggesting that the health of these cellular powerhouses plays a pivotal role in the condition. This review meticulously examines the effects of mitochondrial dysfunction specifically in ovarian granulosa cells, delving into the intricate mechanisms of action that contribute to the development and progression of PCOS, as well as identifying potential therapeutic targets that could be explored for effective treatment. By thoroughly analyzing the relevant literature and synthesizing findings from various studies, this paper aims to provide new insights into the multifaceted nature of PCOS research and promote advancements in clinical treatment strategies that could ultimately improve the health and well-being of women affected by this disorder.